ANALYSIS OF MATERIALS, METHODS AND STRATEGIES AND THEIR ROLE IN THE TEACHING AND LEARNING PROCESS - Marsaoly, Muhammad Isya (Four Son Scholarship, 2023)
This study aims to analyze the material, methods and strategies and their role in the teaching and learning process. The research method used is qualitative research and use descriptive data analysis as a tool in describing this research. The presence of Information Technology has an impact on changing all aspects of Indonesian life, especially in the learning process. Learning is the interaction between educators and learners in a learning environment. In the process of interaction carried out by educators with learners in the digital era today has a difference compared to before. Where the learning process (interaction) takes place is starting to shift into digital learning interactions. So that changes that occur in the learning process from generation to generation required learning strategies in accordance with the development of Information Technology. The results of the analysis of the material, methods and strategies are closely related and interdependent with each other in the teaching and learning process which in essence the three components are aimed at achieving student learning goals, such as in the selection of learning strategies must be in line with the learning method if the two components are not in line with, vice versa, if the two components are in line and the learning material is not organized properly, the results will not be in accordance with the intended purpose and the learning process becomes undirected.